PENGEMBANGAN MEDIA PEMBELAJARAN BERHITUNG UNTUK ANAK MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Bayu Fajar Pratama; Lailatul Husniah (Matrix: Jurnal Manajemen Teknologi dan Informatika, 2018)
Counting learning media for children is a medium of numbers recognition for children that can be used on Android smartphone platform. This learning medium contains some materials such as unit number, tens, sum, and subtraction. In making this learning media required application or game engine that can combine between text, images, animation, and sound. This research uses Unity3D game engine developed by Multimedia Development Life Cycle method with 6 stages: concept, design, material collecting, manufacture, testing, and distribution. This research is intended to develop the application of numeracy learning for children. The applications generated by this study have been tested using blackbox testing that produces a successful indicator in each test.